A study of the impact of policy-based agricultural insurance on farmers’ willingness to adopt pro-environmentally production behaviors: evidence from Jiangxi Province in China - Li, Yanzhe; Hu, Kai; Wu, Huiping; Luo, Wei; Li, Zhaoguang (Frontiers in Sustainable Food Systems, 2025)
IntroductionThe problem of agricultural non-point source pollution in China seriously affects the sustainability of grain production and poses a great threat to food security. The key to solving the problem of agricultural non-point source pollution is to change farmers’ past agricultural production methods at the source of production and make them adopt pro-environmental agricultural production behaviors. Policy-based agricultural insurance can incentivize farmers’ willingness to adopt pro-environmental production behaviors by reducing their production risks and protecting their agricultural income.MethodsBased on the theory of farmers’ behavior and the theory of planned behavior, this paper empirically analyzes the influence mechanism of policy-based agricultural insurance on farmers’ willingness to adopt pro-environmental production behaviors in Jiangxi Province, China, through the establishment of the OLS model and the Ordered-Logit model. In addition, this paper also explores the mediating roles of planting scale, planting structure and risk attitude through the mediating effect model and Bootstrap method.ResultsThe main findings of this paper are as follows: (1) Policy-based agricultural insurance can effectively enhance farmers’ adoption willingness to adopt pro-environmental production willingness. (2) Policy-based agricultural insurance can enhance farmers’ pro-environmental production willingness by incentivizing them to expand the scale of planting. (3) Policy-based agricultural insurance can increase farmers’ pro-environmental production willingness by changing their risk attitudes and increasing their risk preferences.DiscussionBased on the results of the study, this paper suggests that the government should continue to optimize the policy-based agricultural insurance products, expand the coverage, improve the payout process, increase the payout capacity, and enhance its stimulating effect on farmers’ willingness to adopt pro-environmental production behaviors.